SWACHH BHARAT INITIATIVES - P.SUGANYA, Dr.B.REVATHY (International Journal of Advanced Science and Technology, 2020)
The paper is an attempt to document the stages of implementation of Swachh Bharat initiatives acrossthe states in India; Swachh Bharat Abhiyan (SBA) was started as and initiative by the IndianGovernment on 2nd October 2014 as part of sanitation and cleanliness drive across our country. It triesto provide a comprehensive review of various activities undertaken through Swachh Bharat initiativesin the rural and urban areas across India. The data used for this survey are collected from officialsources of Government of India and other documents and reports available at the public domain. Anattempt is made to find out the implementation of Swachh Bharat Abhiyan scheme in TirunelveliDistrict. Socio economic profile of respondents regarding their gender, locality, type of family, religion,age and income are analyzed. Survey method was adopted for the study. Using simple random samplingtechnique a sample of 70 beneficiaries of SBA schemeis chosen for the survey. Findings revealed thatthe beneficiaries did not differ in their awareness about clean India programme gender, location, typeof the family, religion, age and income. The level of awareness about Swachh Bharat Abhiyan schemewas at a moderate level. This paper also highlights the success cases of Swachh Bharat implementationin Tirunelveli and brings out the important challenges in the operationalization of the programme inthe surrounding areas.